Pendampingan Penguatan Kemampuan Bahasa Anak Usia Dini Melalui Pelatihan Mendongeng Bagi Pendidik dan Orang Tua - Sari, Dita Kumala (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
The purpose of this mentoring activity is to introduce storytelling activities in developing language skills in early childhood so that children have a larger vocabulary than what they have mastered. This service is carried out with a counseling and training approach. The mentoring period is September 14, 2024. The results of the listening ability service activity, children learn to retell the characters, places and content of the story that has been heard when the teacher tells the story. Speaking ability, children learn to speak to imitate the teacher's words while reading the story. Reading ability, children can practice their word reading skills through understanding the story presented. There needs to be cooperation and encouragement from both parents and teachers to motivate children to have an interest in reading so that the literacy culture in Indonesia can increase. By routinely reading fairy tales to children, children will be interested in reading culture.